Effect of acute detraining following two types of resistance training on strength performance and body composition in trained athletes - Dariush Vatanı; Masoumeh Azizi; Uones Bakhtıary; Vahid Tadıbı (Selcuk University, 2014)
The purpose of this study was to investigate the effects of short-term detraining after two different protocols of resistance training on maximal strength and body composition in trained men. Participants were 30 male student athletes who were divided into two experimental groups. Group (I) performed resistance training with a low intensity and high volume (LIHV) and group (II) low volume and high intensity (HILV) for six weeks and then experienced 2 weeks detraining. Subjects were evaluated three phases in pretest, posttest, and end of the detraining period. Results demonstrated that after six weeks of resistance training enhanced significantly maximal strength while Body Mass Index (BMI) and percent of body significantly decreased in both groups. However, after two weeks of detraining, maximal strength significantly decreased in all of movements but BMI and percent of body significantly increased in both groups. Nevertheless, maximal strength in all of movements remained significantly higher than pre-exercise levels in both groups. BMI had no meaningful differences with pre-exercise values in both groups, and percent of body fat remained significantly lower than pre-exercise values, only in group (I). However significant differences were not seen between two groups after training and detraining periods but based on data it could be suggested that detraining related strength losses develop less followed HILV protocol.